1997
DOI: 10.1093/treephys/17.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Picea, Pinus and Pseudotsuga roots to heterogeneous nutrient distribution in soil

Abstract: The spatial distribution of plant-available mineral nutrients in forest soils is often highly heterogeneous. To test the hypothesis that local nutrient enrichment of soil leads to increased root proliferation in the nutrient-rich soil zone, we studied the effects of nutrient enrichment on the growth and nutrient concentrations of Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco), Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies (L.) Karst.) roots. Three-year-old seedlings were grown for 9 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 35 publications
6
61
0
2
Order By: Relevance
“…Similar to our results, several studies did not find plasticity in tree root morphological traits (George et al 1997;Espeleta and Donovan 2002;Leuschner et al 2004;Meier and Leuschner 2008;Hertel et al 2013), whereas others did. For example, Fahey and Hughes (1994) and Ostonen et al (2007a) found lower SRL on resource-poor compared to resource-rich soils, whereas Ostonen et al (2007b) observed the opposite response.…”
Section: Fine-root Morphological Traits Do No Differ Between Soil Typessupporting
confidence: 91%
“…Similar to our results, several studies did not find plasticity in tree root morphological traits (George et al 1997;Espeleta and Donovan 2002;Leuschner et al 2004;Meier and Leuschner 2008;Hertel et al 2013), whereas others did. For example, Fahey and Hughes (1994) and Ostonen et al (2007a) found lower SRL on resource-poor compared to resource-rich soils, whereas Ostonen et al (2007b) observed the opposite response.…”
Section: Fine-root Morphological Traits Do No Differ Between Soil Typessupporting
confidence: 91%
“…fertilization when compared to conditions without fertilization despite the same watering regimes. These results indicated that supply fertilization treatments could reduce the growth of roots as well as promote the growth of shoots, especially the growth of leaves, as also previously observed (George et al, 1997;Berger and Glatzel, 2001;Ewers et al, 2001;Trapeznikov et al, 2003;Coleman et al, 2004;Kaakinen et al, 2004). Moreover, nitrogen deficiency suppresses growth rate and leaf photosynthesis (Zhao et al, 2003), and N pulse increases photosynthetic rates and thus growth (Warren et al, 2004).…”
Section: Tablesupporting
confidence: 80%
“…Kong et al (2014) has shown that root diameter and RTD have greater Blomberg's K values (an index assessing the phylogenetical conservativeness of different biological traits) (Blomberg et al 2003) among 14 root functional traits, implying that they are phylogenetically conservative within species and poorly plastic in response to changing soil environment. SRL is considered to be indicative of interspecific differences in environmental change response (Ostonen et al 2007), but it may be less responsive to N addition within species (George et al 1997;Mei et al 2010). Our results showed that SRL did not change with N addition (data not shown).…”
Section: Discussionmentioning
confidence: 49%